Thyroid Gland and Pregnancy – Clinical Update - Mladenovic, Violeta; Shah, Ravi; Medenica, Sanja; Dutta, Pinaki; Zankovic, Nikola; Aksam, Slavica; Ghosh, Jayaditya; Hussain, MdSadam; Gluvic, Zoran (Hormone and Metabolic Research, 2025)
Thyroid function undergoes significant alterations during pregnancy due to changes in hormone levels and higher metabolic demands. The thyroid gland in pregnancy enlarges by 10%; however, in iodine-deficient areas, this growth might reach 40%. Elevated levels of human chorionic gonadotropin (hCG) in early pregnancy leads to increased thyroid hormone production. While triiodothyronine (T3) and thyroid-stimulating hormone (TSH) do not cross the placenta, thyroxine (T4) does. Thyroid hormone demands peaks between weeks 16 and 20 of pregnancy and remains high until delivery. There is a rise in the levels of thyroxine-binding globulin (TBG), during the period of pregnancy, raising total T4 and T3 levels while TSH levels usually decrease. Pregnancy-related thyroid disorders, such as hypothyroidism, hyperthyroidism, and autoimmune thyroid diseases (AITD), carry the potential to impair the well-being of both the child as well as the mother. A range of 5–20% of women belonging to the reproductive age group have AITD, which can be associated with the possibility of infertility, miscarriages, and/or poor pregnancy outcomes. If improperly managed, overt hypothyroidism can cause severe complications such as developmental delay and preeclampsia. Effective management requires regular monitoring and appropriate treatment adjustment. Treatment for hypothyroidism involves levothyroxine, whereas cautious use of antithyroid medications is advised for hyperthyroidism. Postpartum thyroiditis (PPT), an autoimmune condition occurring after childbirth, requires careful management to address both hyperthyroid and hypothyroid phases. A comprehensive understanding and management of these conditions are critical for optimizing maternal and fetal health outcomes. Thyroid disorders are common in women of reproductive age group.
Keywords: thyroid gland; pregnancy; autoimmune thyroid diseases; hypothyroidism; post-partum thyroiditis